2005 Conference on High Density Microsystem Design and Packaging and Component Failure Analysis 2005
DOI: 10.1109/hdp.2005.251415
|View full text |Cite
|
Sign up to set email alerts
|

Localized Micro-Inserts Connection for Smart Card Secure Micro Packaging

Abstract: Smart card integrated circuits are never completely immune against any invasive attack (chemical, physical or energetic), and a hardware protection of the chip could be necessary. One solution consists in shielding the devices at the wafer level with a silicon structured cap (Sishell™). In order to increase security, this cap can also comport active functions. In this case electrical connections between the two wafers are necessary. This paper presents a new solution to interconnect two wafers, compatible with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…This 2D connection structure has been tested and evaluated in a previous work [4]. It has been shown that an electrical efficiency of more than 90% can be achieved.…”
Section: ) From 2d To 3d Integrationmentioning
confidence: 94%
See 1 more Smart Citation
“…This 2D connection structure has been tested and evaluated in a previous work [4]. It has been shown that an electrical efficiency of more than 90% can be achieved.…”
Section: ) From 2d To 3d Integrationmentioning
confidence: 94%
“…Among these approaches, the most conventional use fusible bumps which, once soldered to the pad, enable connection between dies. The LETI has over the last few years developed a technology implementing µbumps located (figures 1 and 2) on the connection pads [3,4]. These small spikes are Nickel-base and are formed at the interconnection point between the two circuits by a combination of lithography and electrolytic plating.…”
Section: ) From 2d To 3d Integrationmentioning
confidence: 99%
“…The combination of multi wavelengths OCT and NIR microscopy has been used to control a die to wafer stacking process. Figure 14 shows results obtained on a test vehicle using micro-inserts for interconnection 6 . A Kelvin bump pattern which includes a matrix of 16 micro-inserts has been used for electrical resistance measurement 7 .…”
Section: Die Stackingmentioning
confidence: 99%